Film directing shot by shot : visualizing from concept to screen - Katz, Steven D. (Michael Wiese Productions in conjunction with Focal Press, 1991)
This international best-seller is filled with visual techniques for filmmakers and screenwriters who want to expand their stylistic knowledge.